1997
DOI: 10.1063/1.365498
|View full text |Cite
|
Sign up to set email alerts
|

High resistive nanocrystalline Fe-M-O (M=Hf, Zr, rare-earth metals) soft magnetic films for high-frequency applications (invited)

Abstract: Microstructure, soft magnetic properties, and applications of high resistive Fe-M-O (M=Hf, Zr, rare-earth metals) were studied. The Fe-M-O films are composed of bcc nanograins and amorphous phases with larger amounts of M and O elements which chemically combine each other. Consequently, the amorphous phases have high electrical resistivity. The compositional dependence of magnetic properties, electrical resistivity, and structure have been almost clarified. For example, the high magnetization of 1.3 T, high pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(81 citation statements)
references
References 11 publications
3
78
0
Order By: Relevance
“…Controlling this process to achieve desirable properties in terms of grain size, crystal phase, purity of metal grains, composition of the ceramic matrix, volume fraction of metal, and stress is difficult. Nonetheless, reactive sputtering has demonstrated that such a material can, in fact, have high performance at high frequencies, including relative permeability of 170 and É of 60 at 100 MHz, with permeability maintained to about 1 GHz [30], attractive properties for both power and RF applications. In [24], an inductor application of these materials in an efficient high-frequency dc-dc converter was demonstrated at low power density.…”
Section: Magnetic Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Controlling this process to achieve desirable properties in terms of grain size, crystal phase, purity of metal grains, composition of the ceramic matrix, volume fraction of metal, and stress is difficult. Nonetheless, reactive sputtering has demonstrated that such a material can, in fact, have high performance at high frequencies, including relative permeability of 170 and É of 60 at 100 MHz, with permeability maintained to about 1 GHz [30], attractive properties for both power and RF applications. In [24], an inductor application of these materials in an efficient high-frequency dc-dc converter was demonstrated at low power density.…”
Section: Magnetic Materialsmentioning
confidence: 99%
“…Although conventional powdered-metal materials have limited power performance at frequencies this high, recent work has shown that higher performance is possible in vacuum deposited materials with nanoscale particles of Co or Fe [27], [28], [29], [30]. These materials have been fabricated by reactive sputtering.…”
Section: Magnetic Materialsmentioning
confidence: 99%
“…Meanwhile, the exchange coupling between neighboring magnetic nanoparticles can overcome the anisotropy and demagnetizing effects, resulting in better soft magnetic properties than conventional materials [I]. Based on this idea, nanocomposite thin films with significantly improved high frequency properties have been developed [2,3]. However, the thin film techniques cannot be used to produce bulk components.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate the applications in high-frequency devices, much research has been done on ferromagnetic material [1][2][3] . For practical applications using relative permeability, µr, such as suppression of randomly polarized electromagnetic wave noise and impedance control of circuits 2-dimensional-randomly arranged on a circuit board, magnetic materials with isotropic magnetic properties are required.…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%